Strategi Pengurangan Konflik Antrian Armada Melalui Visualisasi Informasi dan Validasi Dokumen di PT. SGB Bogor - Ardianto, Rizal; Rachmanto, Danny Dwi; Puspita, Feni Ira; Novelia, Adinda Sukma; Fatimah, Siti (Jurnal TRINISTIK: Jurnal Teknik Industri, Bisnis Digital, dan Teknik Logistik, 2025)
Irregularities in truck queueing during the loading process at the Finished Goods Warehouse Department of PT. SGB have led to repeated complaints from logistics partners, disrupting operational efficiency and damaging the company’s reputation. This study aims to identify the root causes of the issue and propose corrective actions using the Theory of Constraints (ToC) approach. The methods employed include direct observation, in-depth interviews, and structured brainstorming sessions. The analysis revealed three main root causes: the absence of updated queue information for drivers, lack of a standardized document verification procedure, and unavailability of clear priority loading information. The implemented solutions consisted of queue information boards, a ticketing system managed by security personnel, and strengthening the role of warehouse team leaders in communication and oversight. Evaluations conducted from June to February 2025 showed a significant reduction in complaints, improved queue discipline, and decreased overtime costs. This study recommends standardizing operating procedures (SOPs), conducting regular training sessions, and adopting a digital queuing system as a long-term sustainability strategy.